Duraplasty of PHBV/PLA/Col membranes promotes axonal regeneration by inhibiting NLRP3 complex and M1 macrophage polarization in rats with spinal cord injury. Issue 9 (20th July 2020) - Zhao, Tengfei; Xu, Kan; Wu, Qionghua; Wang, Chenggui; Xiao, Shining; Li, Heyangzi; He, Teng; Wang, Linlin; Li, Fangcai; Chen, Qixin
Abstract: Duraplasty after decompression decreases the lesion size and scar formation, promoting better functional recovery, but the underlying mechanism has not been clarified. Here, we fabricated a series of poly(hydroxybutyrate‐co‐hydroxyvalerate)/polylactic acid/collagen (PHBV/PLA/Col) membranes and cultured them with VSC4.1 motor neurons. The material characteristics and in vitro biological characteristics were evaluated. In the subcutaneous implantation test, PHBV/PLA/COl scaffolds supported the cellular infiltration, microvasculature formation, and decreased CD86‐positive macrophage aggregation. Following contusion spinal cord injury at T10 in Sprague‐Dawley rats, durotomy was performed with allograft dura mater or PHBV/PLA or PHBV/PLA/Col membranes. At 3 days post‐injury, Western blot assay showed decreased the expression of the NLRP3, ASC, cleaved‐caspase‐1, IL‐1β, TNF‐α, and CD86 expression but increased the expression of CD206. Immunofluorescence demonstrated that duraplasty with PHBV/PLA/Col membranes reduced the infiltration of CD86‐positive macrophages in the lesion site, decreased the glial fibrillary acidic protein expression, and increased the expression of NF‐200. Moreover, duraplasty with PHBV/PLA/Col membranes improved locomotor functional recovery at 8 weeks post‐injury. Thus, duraplasty with PHBV/PLA/Col membranes decreased the glial scar formation and promoted axon growth by inhibiting inflammasome activation and modulating macrophage polarization in acute spinal cord injury.